Servitization as a concept for managing the development of small and medium-sized enterprises = Serwicyzacja jako koncepcja zarządzania rozwojem małych i średnich przedsiębiorstw - Lachiewicz, Stefan; Matejun, Marek; Pietras, Paweł; Szczepańczyk, Maciej (Zielona Góra: Faculty of Economics and Management Press)
The aim of the article is to present the key features, stages, advantages and threats of servitization as a concept for managing the development of small and medium-sized enterprises. A literature review and empirical research carried out in the form of a case study of the medium-sized company Mikomax sp. z o.o. from Poland served to achieve the aim of the article.
Keywords: serwicyzacja; usługi; zarządzanie rozwojem firmy; mały biznes; współczesne koncepcje zarządzania; servitization; service; company development management; small business; modern concepts of management